1993
DOI: 10.1051/apido:19930605
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric identification of Africanized and European honey bees using large reference populations

Abstract: Summary — New discriminant analysis procedures have been presented to identify Africanized and European honey bees. These procedures are founded on data from 2 103 samples of honey bees collected from colonies at several locations in the western hemisphere and Kangaroo Island, Australia. Various univariate and multivariate analyses have been used to select the morphological characteristics and the groups of characteristics to be used in the analysis. The multivariate discriminant analysis correctly ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
6

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 12 publications
1
52
0
6
Order By: Relevance
“…Southern Arizona has an established feral population of Africanized bees that originated from the northward expansion of Africanized populations following the introduction of A. mellifera scutellata into Brazil (Fewell and Bertram 2002;Schneider et al 2004a;Rabe et al 2005). Africanization of the bees used in this study was confirmed using mitochondrial DNA (Nielsen et al 2000) and morphometric analyses (Rinderer et al 1993). All source colonies for this study were maintained in apiaries at the Carl Hayden Bee Research Center in Tucson, AZ, USA.…”
Section: Methodsmentioning
confidence: 77%
“…Southern Arizona has an established feral population of Africanized bees that originated from the northward expansion of Africanized populations following the introduction of A. mellifera scutellata into Brazil (Fewell and Bertram 2002;Schneider et al 2004a;Rabe et al 2005). Africanization of the bees used in this study was confirmed using mitochondrial DNA (Nielsen et al 2000) and morphometric analyses (Rinderer et al 1993). All source colonies for this study were maintained in apiaries at the Carl Hayden Bee Research Center in Tucson, AZ, USA.…”
Section: Methodsmentioning
confidence: 77%
“…Balling functions [3] and the AFUSDA programme [30]. PAs were used to classify colonies in accordance with the categories of Rinderer et al [30], as modified by Quezada-Euán et al [23], i.e.…”
Section: Resultsmentioning
confidence: 99%
“…PAs were used to classify colonies in accordance with the categories of Rinderer et al [30], as modified by Quezada-Euán et al [23], i.e. : Africanized (A), Africanized with evidence of European introgression (AE); European with evidence of African introgression (EA); and European (E).…”
Section: Resultsmentioning
confidence: 99%
“…Rinderer et al (1990) compared morphometric measurements of workers of Africanized and European bees and of their F 1 progeny. Rinderer et al (1993) also used large reference populations to develop patterns for the recognition of intermediate individuals; they intercrossed Africanized and Eu-ropean bees, producing 192 hybrid colonies. Based on morphometric analyses, they concluded that most of these hybrid colonies were intermediate (midway) between the groups.…”
Section: Introductionmentioning
confidence: 99%